Total Anomalous Systemic Venous Drainage with Heterotaxia Syndrome: A Rare Case - Ali Yildirim; Pelin Kosger; Gokmen Ozdemir; Birsen Ucar; Zubeyir Kilic (Case Reports in Cardiology)
Total anomalous systemic venous return is a very rare anomaly, where vena cava inferior, vena cava superior, and coronary sinus drain into left atrium. Two-day-old male baby was admitted with cyanosis and tachypnea after the birth. Left atrial isomerism with anomalous systemic venous drainage was found on echocardiographic examination. We present an unusual case of total anomalous systemic venous drainage in to the left atrium.